Electronic Devices Using Open Framework Materials - Allendorf, Mark D.; Dong, Renhao; Feng, Xinliang; Kaskel, Stefan; Matoga, Dariusz; Stavila, Vitalie (Chemical Reviews, 2020)
Open framework materials (OFM) constitute a large and growing class of nanoporous crystalline structures that is attracting considerable attention for electronic device applications. This review summarizes the most recent reports concerning electronic devices enabled by either of the two primary categories of OFM, metal-organic frameworks (MOFs) and covalent-organic frameworks (COFs). Devices in which the OFM plays an active role (as opposed to acting only as a selective sorbent or filter) are the principal focus, with examples cited that include field-effect transistors, capacitors, memristors, and a wide variety of sensing architectures. As a brief tutorial, we also provide a concise summary of various methods of depositing or growing OFM on surfaces, as these are of crucial importance to the deployment of electronic OFM. Finally, we offer our perspective concerning future research directions, particularly regarding what in our view are the biggest challenges remaining to be addressed. On the basis of the literature discussed here, we conclude that OFM constitute a unique class of electronic materials with characteristics and advantages that are distinct from either conventional inorganic semiconductors or organic conductors. This suggests a bright future for these materials in applications such as edge computing, resistive switching, and mechanically flexible sensing and electronics.
CRIS-Team Scopus Importer:2022-04-14